Toward improved simulation of river operations through integration with a hydrologic model. (August 2016) - Morway, Eric D.; Niswonger, Richard G.; Triana, Enrique
Abstract: Advanced modeling tools are needed for informed water resources planning and management. Two classes of modeling tools are often used to this end–(1) distributed-parameter hydrologic models for quantifying supply and (2) river-operation models for sorting out demands under rule-based systems such as the prior-appropriation doctrine. Within each of these two broad classes of models, there are many software tools that excel at simulating the processes specific to each discipline, but have historically over-simplified, or at worse completely neglected, aspects of the other. As a result, water managers reliant on river-operation models for administering water resources need improved tools for representing spatially and temporally varying groundwater resources in conjunctive-use systems. A new tool is described that improves the representation of groundwater/surface-water (GW-SW) interaction within a river-operations modeling context and, in so doing, advances evaluation of system-wide hydrologic consequences of new or altered management regimes. Graphical abstract: Highlights: The river/reservoir operations model MODSIM is coupled to MODFLOW. Models simulate physics based hydrology and priority/rule based water allocation. Coupling uses a Picard iteration and an implicit, mass conservative solution. Model simulates conjunctive use of surface water and groundwater. Helps evaluate groundwater sustainability resulting from alternative management.